Acetate and Potassium Modulate the Stationary-Phase Activation of lrgAB in Streptococcus mutans - Ahn, Sang-Joon; Desai, Shailja; Blanco, Loraine; Lin, Min; Rice, Kelly C. (Frontiers in Microbiology, 2020)
Fluctuating environments force bacteria to constantly adapt and optimize the uptake of substrates to maintain cellular and nutritional homeostasis. Our recent findings revealed that LrgAB functions as a pyruvate uptake system in Streptococcus mutans, and its activity is modulated in response to glucose and oxygen levels. Here, we show that the composition of the growth medium dramatically influences the magnitude and pattern of lrgAB activation. Specifically, tryptone (T) medium does not provide a preferred environment for stationary phase lrgAB activation, which is independent of external pyruvate concentration. The addition of pyruvate to T medium can elicit PlrgA activation during exponential growth, enabling the cell to utilize external pyruvate for improvement of cell growth. Through comparison of the medium composition and a series of GFP quantification assays for measurement of PlrgA activation, we found that acetate and potassium (K+) play important roles in eliciting PlrgA activation at stationary phase. Of note, supplementation of pooled human saliva to T medium induced lrgAB expression at stationary phase and in response to pyruvate, suggesting that LrgAB is likely functional in the oral cavity. High concentrations of acetate inhibit cell growth, while high concentrations of K+ negatively regulate lrgAB activation. qPCR analysis also revealed that growth in T medium (acetate/K+ limited) significantly affects the expression of genes related to the catabolic pathways of pyruvate, including the Pta/AckA pathway (acetate metabolism). Lastly, stationary phase lrgAB expression is not activated when S. mutans is cultured in T medium, even in a strain that overexpresses lytST. Taken together, these data suggest that lrgAB activation and pyruvate uptake in S. mutans are connected to acetate metabolism and potassium uptake systems, important for cellular and energy homeostasis. They also suggest that these factors need to be implemented when planning metabolic experiments and analyzing data in S. mutans studies that may be sensitive to stationary growth phase.